Muscle mass, strength, and physical performance predicting activities of daily living: a meta‐analysis. Issue 1 (1st December 2019) - Wang, Daniel X.M.; Yao, Jessica; Zirek, Yasar; Reijnierse, Esmee M.; Maier, Andrea B.
Abstract: Background Activities of daily living (ADLs) and instrumental activities of daily living (IADLs) are essential for independent living and are predictors of morbidity and mortality in older populations. Older adults who are dependent in ADLs and IADLs are also more likely to have poor muscle measures defined as low muscle mass, muscle strength, and physical performance, which further limit their ability to perform activities. The aim of this systematic review and meta‐analysis was to determine if muscle measures are predictive of ADL and IADL in older populations. Methods A systematic search was conducted using four databases (MEDLINE, EMBASE, Cochrane, and CINAHL) from date of inception to 7 June 2018. Longitudinal cohorts were included that reported baseline muscle measures defined by muscle mass, muscle strength, and physical performance in conjunction with prospective ADL or IADL in participants aged 65 years and older at follow‐up. Meta‐analyses were conducted using a random effect model. Results Of the 7760 articles screened, 83 articles were included for the systematic review and involved a total of 108 428 (54.8% female) participants with a follow‐up duration ranging from 11 days to 25 years. Low muscle mass was positively associated with ADL dependency in 5/9 articles and 5/5 for IADL dependency. Low muscle strength was associated with ADL dependency in 22/34 articles and IADL dependency in 8/9 articles. Low physical performance was associated with ADL dependency in 37/49 articles and with IADL dependency in 9/11 articles. Forty‐five articles were pooled into the meta‐analyses, 36 reported ADL, 11 reported IADL, and 2 reported ADL and IADL as a composite outcome. Low muscle mass was associated with worsening ADL (pooled odds ratio (95% confidence interval) 3.19 (1.29–7.92)) and worsening IADL (1.28 (1.02–1.61)). Low handgrip strength was associated with both worsening ADL and IADL (1.51 (1.34–1.70); 1.59 (1.04–2.31) respectively). Low scores on the short physical performance battery and gait speed were associated with worsening ADL (3.49 (2.47–4.92); 2.33 (1.58–3.44) respectively) and IADL (3.09 (1.06–8.98); 1.93 (1.69–2.21) respectively). Low one leg balance (2.74 (1.31–5.72)), timed up and go (3.41 (1.86–6.28)), and chair stand test time (1.90 (1.63–2.21)) were associated with worsening ADL. Conclusions Muscle measures at baseline are predictors of future ADL and IADL dependence in the older adult population.